2022
DOI: 10.3393/ac.2021.00619.0088
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and outcomes of colorectal cancer surgery by age in a tertiary center in Korea: a retrospective review

Abstract: Purpose: Colorectal cancer (CRC) occurs in all age groups, and the application of treatment may vary according to age. The study was designed to identify the characteristics of CRC by age.Methods: A total of 4,326 patients undergoing primary resection for CRC from September 2006 to July 2019 were reviewed. Patient and tumor characteristics, operative and postoperative data, and oncologic outcome were comparedResults: Patients aged 60 to 69 years comprised the largest age group (29.7%), followed by those aged 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Open surgery was also found to be a risk factor for SSI in colorectal surgery in this study, in line with the results of other studies; when open and laparoscopic approaches were compared, a notable reduction in SSI was observed when the laparoscopic approach was employed. [27][28][29] In the laparoscopic approach, not only minimal incision but also the use of a wound protector appears to be effective in reducing SSI, and wound protector use is advocated even in open incision surgeries. 30,31 Although some SSI bundles include a wound protector, it cannot be used for the open approach in Korea, because the Korean insurance system does not cover the cost.…”
Section: Discussionmentioning
confidence: 99%
“…Open surgery was also found to be a risk factor for SSI in colorectal surgery in this study, in line with the results of other studies; when open and laparoscopic approaches were compared, a notable reduction in SSI was observed when the laparoscopic approach was employed. [27][28][29] In the laparoscopic approach, not only minimal incision but also the use of a wound protector appears to be effective in reducing SSI, and wound protector use is advocated even in open incision surgeries. 30,31 Although some SSI bundles include a wound protector, it cannot be used for the open approach in Korea, because the Korean insurance system does not cover the cost.…”
Section: Discussionmentioning
confidence: 99%
“…To determine whether the COVID-19 pandemic has compromised the long-term oncologic outcomes of colorectal cancer, we must await their long-term reports. Other factors, such as the number of harvested lymph nodes, lymphatic invasion, vascular invasion, perineural invasion, and preoperative obstruction, may also be associated with oncologic outcomes [13,39,50] in addition to the pathologic stage. However, many studies have not reported these variables.…”
Section: Discussionmentioning
confidence: 99%
“…Colorectal cancer (CRC) is the third most common cancer type and the second cause of cancer-related mortality in the analysis of global cancer statistics [1]. The overall survival of patients with CRC has improved with the development of multimodal treatments and new chemotherapeutic drugs [2][3][4]. In an analysis of the Surveillance, Epidemiology, and End Results (SEER) database from 2010 to 2019, ageadjusted rates for new CRC declined by 1.8% annually, whereas the 5-year survival rate showed a gradual increase [5].…”
Section: Introductionmentioning
confidence: 99%